2014
DOI: 10.1177/0025802414557881
|View full text |Cite
|
Sign up to set email alerts
|

Organ procurement in forensic deaths: French developments

Abstract: Organ procurement and transplantation have grown steadily, and the need for organs will only rise in the future. Increasing the number of potential donors is therefore paramount. However, transplant coordination teams face refusals that can be linked to the contexts of the deaths, especially when they involve legal issues. In France, deaths involving legal proceedings are not uncommon (7-10%). In these cases, the prosecutor is immediately contacted, and makes the decision of whether to remove the involved orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…3 It is for this reason that the French Society of Forensic Medicine set out to develop a national recommendation. This recommendation 5,6 sought to combine 2 interests: first, addressing the shortage of organs and second, fulfilling the requisites of a criminal investigation by standardizing practices. The guideline emerged in early 2013 and is available online at our society's website.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is for this reason that the French Society of Forensic Medicine set out to develop a national recommendation. This recommendation 5,6 sought to combine 2 interests: first, addressing the shortage of organs and second, fulfilling the requisites of a criminal investigation by standardizing practices. The guideline emerged in early 2013 and is available online at our society's website.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of forensic deaths is 7-10% in France, and refusal rate of attorney for removal of organs is 4% 16 . French Forensic Medicine Society published an advisory guideline in 2013 for attorneys to help them to make their decisions.…”
Section: Discussionmentioning
confidence: 99%
“…According to this guideline, agreement protocols are prepared for legal authorities, forensic pathologists, transplant teams and attorney. Thus, forensic physician and transplant teams can act in coordination and forensic pathologist may interfere the process before and after removal of the organs 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In most jurisdictions, the legal DI authorized organ donation while the medical DI played a consulting role. This was the case in Australia, France, the United Kingdom, and some states in the United States (11,13,15,23,28,29,30). Depending on the system, legal bodies may have relied completely on the medical opinion or they may have decided in opposition.…”
Section: ) Legally Trained DI Authority To Veto Medical Decisions To ...mentioning
confidence: 99%
“…Examining the decedent preorgan recovery or attending the organ recovery could facilitate both organ donation and death investigations when there were resources to support this approach. In France, the same DI examined the decedent in the ICU, during the organ recovery surgery, and at autopsy (13,29,30). Protocols from states such as New Jersey, Texas, and Tennessee indicated that DIs could not deny organ donation without attending organ recovery (2,12,17).…”
Section: ) DI Attendance At Organ Recovery As Neededmentioning
confidence: 99%